2021
DOI: 10.1021/acs.jafc.1c01465
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Dietary Fibers Selectively Promote Gut Microbiota to Exert Antidiabetic Effects

Abstract: High intake of dietary fibers was found to be inversely associated with type-2 diabetes (T2D), whereas the difference among different dietary fibers on T2D remains unclear. Therefore, we have investigated the effects of different dietary fibers on T2D. Nine types of dietary fibers were used to investigate and evaluate their effects on type-2 diabetic rats via physiology, genomics, and metabolomics. We found that supplementation with β-glucan, arabinogalactan, guar gum, apple pectin, glucomannan, and arabinoxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Since LF psyllium induced the greatest metabolomic change compared to LF, we performed a (Spearman) correlation between the microbiome and the metabolome data in order to elucidate potential interactions. Gut microbial profile correlates with azoles, organic acids and carbohydrates (Figure 5H) Further exploration of genera modulated by psyllium as determined in the aforementioned microbiome analysis, revealed that Parasutterella and Akkermansia had strong negative correlation with glucose (R −0.67, −0.73 respectively p < 0.05), type 2 diabetes associated metabolites 3-methyl-2-oxovaleric acid (R −0.72, −0.78 respectively p < 0.05), and citrulline (R −0.77, −0.71 respectively p < 0.05) [26,27], whilst Enterorhabdus, Odoribacter and Lachnoclostridium had the opposite effect (Table 3). Full correlation analysis table is given in Supplementary Data (Table S3).…”
Section: Dfs Have a Profound Impact On Cecal Metabolomic Profilementioning
confidence: 99%
“…Since LF psyllium induced the greatest metabolomic change compared to LF, we performed a (Spearman) correlation between the microbiome and the metabolome data in order to elucidate potential interactions. Gut microbial profile correlates with azoles, organic acids and carbohydrates (Figure 5H) Further exploration of genera modulated by psyllium as determined in the aforementioned microbiome analysis, revealed that Parasutterella and Akkermansia had strong negative correlation with glucose (R −0.67, −0.73 respectively p < 0.05), type 2 diabetes associated metabolites 3-methyl-2-oxovaleric acid (R −0.72, −0.78 respectively p < 0.05), and citrulline (R −0.77, −0.71 respectively p < 0.05) [26,27], whilst Enterorhabdus, Odoribacter and Lachnoclostridium had the opposite effect (Table 3). Full correlation analysis table is given in Supplementary Data (Table S3).…”
Section: Dfs Have a Profound Impact On Cecal Metabolomic Profilementioning
confidence: 99%
“…Indole is the precursor of indoxyl sulfate, which linked with cancer, host metabolic disorders, cardiovascular disease, type 2 diabetes, hypertension, and induced intestinal barrier dysfunction [ 42 , 43 , 44 , 45 , 46 , 47 ]. It was reported that dietary supplements of beneficial substances effectively decreased indole-derived metabolites in the host [ 48 , 49 , 50 ]. LPEPS oral administration remarkedly decreased purine and pyrimidine nucleosides, including xanthosine and uridine, in the feces of AOM/DSS-treated C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…LPEPS oral administration decreased 3-hydroxynonanoyl carnitine in the AOM/DSS-treated mice. A number of studies have shown that carnitine was enriched in colon cancer and type 2 diabetes [ 46 , 55 , 56 , 57 , 58 ], while natural active substance supplementation effectively decreased concentration of carnitine in type 2 diabetes [ 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…AG was dissolved with distilled water and prepared into a solution with a concentration of 3.9 mg/ml. The intragastric dose of arabinogalactan solution (A) was 390 mg/kg/day (Nie et al, 2021). The fresh bacterial medium with B. longum (B) or F. prausnitzii (F) was centrifuged and suspended again into a bacterial suspension with sterile PBS.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Sun et al, 2021). Our previous study has shown that AG can increase body weight, reduce fasting glucose, change the relative abundance of gut microbiota, and alleviate impaired glucose tolerance in T2D rats (Nie et al, 2021). However, the role of AG on IR in HFD‐induced mice is still unclear.…”
Section: Introductionmentioning
confidence: 99%